The Duality of Cultural Coping: Endurance as Both Resource and Barrier Among Elderly Residents in Chinese Pension Institutions - Wen Zhang; Jamayah Saili (Journal of Mental Health, 2026)
With the acceleration of population aging in China, the mental health problems of elderly people in pension institutions have become increasingly prominent. However, the existing coping research is dominated by mainstream Western coping theories, without a systematic exploration of the dual function that cultural factors can serve in the coping process. This study aims to explore the dual role of the cultural value of “endurance” (隐忍, yǐn rěn), a Confucian value emphasizing self-restraint and the silent endurance of hardship for the sake of relational harmony, in the psychological adaptation process of elderly people in Jinan pension institutions. Furthermore, it investigates how relational support may influence whether endurance functions as a facilitative or inhibitory coping mechanism. A qualitative study was conducted with elderly people in three pension institutions in Jinan, Shandong Province, China. Using the six-phase thematic analysis developed by Braun and Clarke, the study explored this duality. The study found that the cultural value of endurance served a dual function in the psychological adaptation process, both facilitating accommodative acceptance, meaning reconstruction, and perseverance narratives, and suppressing the expression of emotions and the stigmatization of mental health. Crucially, the presence or absence of relational support determined whether endurance tended to yield adaptive or maladaptive outcomes. The study suggests the need for the supplementation of the Stress and Coping Theory with cultural factors and the development of culturally sensitive psychological services in Chinese pension institutions.